Dinamika Kaligrafi Mushaf Standar Indonesia - Ali Akbar (SUHUF, 2020)
Since the determination of the Indonesian Standard Mushaf in 1984, the Usmani Indonesian Standard Mushaf which was written by the calligrapher Muhammad Syadzeli has been rewritten twice, that was in 2001 by Ustadz Baiquni Yasin and 2019 by Ustadz Isep Misbah. Meanwhile, The Bahriyyah Indonesian Standard Mushaf was written by calligrapher Abdul Razak Muhili, in 1988. In its development, entering the year of 2000s, in line with the development of printing technology, Indonesian Standard Mushaf was printed with modified calligraphy by Usman Taha, a calligrapher of the Syria,. In the recent development, the modified calligraphy of the Medinan Mushaf has been used widely by the publishers of the mushaf in Indonesia, which left far behind the calligraphy written by the local writers. This writing will look at the dynamics of the use or the choice of calligraphy in the Indonesian Standard Mushaf, starting from the historical background of the development of the mushaf in Souteast Asia. The length of the circulation of the printed mushaf of Bombay in Indonesia with the character of the thick calligraphy has brought the impact on the choice of calligraphy of the Indonesian Standard Mushaf, although it was displaced by the style of the Madinah Mushaf calligrapy which is the thin one since the 2000s.